ANALISIS PEMBIAYAAN PENDIDIKAN NASIONAL - Wardani, Dewi Kusuma (Jurnal Inovasi Pendidikan, 2011)
The purposes of this article are to understand (1) the cost of education, (2) the concept of tuition fees and, (3) to determine the cost of education. Data were collected through literature review and document analyses. The result showed that (1) the cost in this article has broad scope, namely all kinds of expenses related to providing education, either in money or goods and labor (which can be measured by money), (2) the cost of education is burden on the community in the expansion and functions of the education system, (3) national educational costs is determined by the number of schools, students, teachers, administrative staff, building maintenance and other operational.